Implementasi E-Swimming Course Pada Usman Harun Sport Center - Ishak Kholil; Nico Dias Palasara; Muhammad Tabrani; Alfiah Nur Hudayani (Prosiding Seminar Nasional Teknoka, 2020)
The development of information technology that occurs at this time can make it easier for someone to do their activities one of them in swimming. Swimming is a sport choice that is usually made by someone as a hobby, lesson and therapy for someone who has physical limitations. Therefore, advances in information technology today are very important, for example information on swimming course services at the Usman Harun Sport Center Swimming Pool. The swimming course service system at the Usman Harun Sports Center still uses a manual system, starting from the registration of new members, the transaction process, student scheduling to report generation. This can cause errors that can occur in the course services due to instability in the timing of members who can change at any time and allow data to be deleted or not stored properly. Based on the problems that have been outlined, the solution to the problem is to create a computerized and integrated system with the internet and websites, namely by designing a system, starting from the creation of UML (Unified Modeling Language) and ERD (Entity Relationship Diagram). So that an activity in a computerized system can be achieved effectively and efficiently and can be more conducive compared to the previous system.